The Role of Investigators in Handling Hate Speech Cases by Children as Criminal Offenders (Case study of Polda Bali) - Adi Putra, Komang Agus Gede; Darma, I Made Wirya (Universitas Medan Area, 2024)
The rapid progress of our time is evident in various aspects of life, including the realm of technology. This progress can have both positive and negative effects on users, especially children who are more susceptible to influence. There is a concern that when children come across news or false information in the media, they may unknowingly spread it without verifying its accuracy. Furthermore, there is a possibility that they may engage in Hate Speech without realizing that it is against the law. This raises a research question: How effective is the implementation of Restorative Justice at the investigator level through juvenile diversion in cases involving criminal Hate Speech? To answer this question, the research follows an empirical method and adopts a case-based approach with supporting facts. The research location for the study is the Bali Regional Police (Polda Bali). The research object focuses on hate speech cases involving child suspects and the effectiveness of Restorative Justice through diversion at the investigator level. Data is collected through interviews and documentary studies. In addressing the research problem, the author focuses on the theory of legal effectiveness, which emphasizes prevention rather than punishment by investigators. Investigators base their actions on Article 1 Paragraph 6 and 7 of Law Number 11 of 2012, which prioritizes Restorative Justice and diversion in handling juvenile cases. The use of Restorative Justice and diversion plays a crucial role in protecting the rights of children and preventing discrimination.